Hearing impairment and associated morphological changes in pituitary adenylate cyclase activating polypeptide (PACAP)-deficient mice - Daniel Balazs Fulop (Nature Portfolio, 2019)
Abstract Pituitary adenylate cyclase activating polypeptide (PACAP) is a regulatory and cytoprotective neuropeptide, its deficiency implies accelerated aging in mice. It is present in the auditory system having antiapoptotic effects. Expression of Ca2+-binding proteins and its PAC1 receptor differs in the inner ear of PACAP-deficient (KO) and wild-type (WT) mice. Our aim was to elucidate the functional role of PACAP in the auditory system. Auditory brainstem response (ABR) tests found higher hearing thresholds in KO mice at click and low frequency burst stimuli. Hearing impairment at higher frequencies showed as reduced ABR wave amplitudes and latencies in KO animals. Increase in neuronal activity, demonstrated by c-Fos immunolabeling, was lower in KO mice after noise exposure in the ventral and dorsal cochlear nuclei. Noise induced neuronal activation was similar in further relay nuclei of the auditory pathway of WT and KO mice. Based on the similar inflammatory and angiogenic protein profile data from cochlear duct lysates, neither inflammation nor disturbed angiogenesis, as potential pathological components in sensorineural hearing losses, seem to be involved in the pathomechanism of the presented functional and morphological changes in PACAP KO mice. The hearing impairment is probably concomitant with the markedly accelerated aging processes in these animals.